Potential of Siamese Weeds (Chromolaena adorate (L) R. M. King dan H.Robinson) as Bioherbisides - Muzaiyanah , Siti (Future Science)
Herbicides increase labor but pollute water sources, destroy soil, and leave toxic residues on agricultural products. Eradication of weeds that are environmentally friendly can be done using bioherbicides, including the allelopathy of Siamese leaves (C. odorata). The research was conducted at the Laboratory of the Indonesian Bean and Tuber Crops Research Institute (BALITKABI) Malang, in April 2017 using a factorial completely randomized design that was repeated three times. The first factor: the concentration of C. odorata extract consisted of: a concentration of 0% (w / v), a concentration of 10% (w / v), a concentration of 20% (w / v), a concentration of 30% (w / v). The second factor: types of commodities, consisting of: soybeans, green beans and rice. The manufacture of simplicia was started with the baking of fresh C. odorata leaves at 65 ?C for 24 hours and then blended. Weighed 60, 40, 20 grams of the simplicia and immersed in 95% ethanol for four hours. Then at each level 200 ml of distilled water was added and filtered with filter paper. The seed testing is done with CD paper which is first moistened with the solution, the seeds are arranged on the CD paper and set up. During germination the moisture of the paper is maintained by giving 10 ml of the extract solution according to each treatment level. The variables observed were radical length (root), plumule length, and number of leaves at 4, 7 and 10 hours. The results showed that C. odorata leaf extract with a concentration of 20% (w / v) and 30% (w / v) was due to bioherbicides which can control weed growth.